Immune stimulating and galectin-3 inhibitory effects of a hydrophilic polysaccharide nutraceutical from Tinospora cordifolia - Cheppail Ramachandran; Karl-Werner Quirin; Enrique Escalon; Steven J Melnick (International Journal of Phytomedicine, 2020)
Tinospora cordifolia is an important ayurvedic herb known for its immune stimulating effect. In this investigation, we describe the galectin-3 inhibitory and immune stimulating properties of a novel water-soluble nutraceutical made from Tinospora cordifolia stem. This proprietary extract (T2CA) had a total yield of 6% and contained 86.9% carbohydrates with a high proportion of patented (1,4)-α-D-glucan in it. The T2CA activated T-cytotoxic and NK cells significantly contributing to its immune stimulating effect. Moreover, T2CA induced the activation of functional NK cells in human lymphocyte cultures that in turn contributed to the death of K562 leukemic cells in a dose-dependent manner in co-culture experiments. T2CA inhibited the expression of phosphorylated galectin-3 expression in human glioblastoma cell line which in turn inhibits the activity of MMP2 and MMP9 proteins in zymography investigations and inhibits migration of cancer cells in in vitro scratch assay. Western blot hybridization studies showed that T2CA downregulates the expression of total gal 3 proteins and extended the survival of AKR/J mice injected with Ehrlich ascites tumor cells in the Kepler-Meier survival curve analysis. The inhibitory effect of T2CA on phopho-galectin-3 expression and the activation of T-cytotoxic and NK cells suggested its protective effects against pathogenic infections and human malignancies via its immune stimulating mechanisms.